Corrigendum to "Existence and some properties of solutions for degenerate elliptic equations with exponent variable" [Nonlinear Anal. 98 (2014) 146–164]. (November 2015) - Ho, Ky; Sim, Inbo
Abstract: We restate Theorem 4.2 and Lemma 4.3 in [1] a little differently and give a proof of Lemma 4.3 and replace corresponding parts in the proof of Theorem 4.2.